Primary health care and alcohol - Seppa, Kaija (Zdravstveno varstvo, 2011)
In his famous novel "Anna Karenina" Konstantin Levin, a farmer who is commonlyconsidered to represent the author Leo Tolstoy himself, listens to another farmerćs opinions on the land reform. He highly respects these opinions which, as he says, ćhad been brought not by a desire of finding some exercise for an idle brain, but a thought which had grown up out of the conditions of his lifeć. Researchers and policy makers, far from the realitiesof primary health care, seem to be more interested in brief alcohol interventions for hazardous drinkers than do general practitioners or other professionals working in this setting. Should brief intervention be removed tosome other setting, buried forever as not being suitable for real life, or would it just now be perfect time for general practitioners and nurses in primary health care to take command of brief interventions and make it suitable for their own setting?
Keywords: alkohol; alkoholizem; družinska medicina; medicinske sestre; zdravstveno varstvo